JALAN MENUJU KELAHIRAN KESULTANAN PALEMBANG (1675) - Dhita, Aulia Novemy; Nofradatu, Salsabila (Estoria: Journal of Social Science and Humanities, 2021)
The Palembang Sultanate was born as a result of the less harmonious relationship between Palembang and Mataram. This explains that in the course of its history, Palembang had a relationship with the kingdom in Java. This study aims to describe the relationship of Palembang with Java before the birth of the Palembang Sultanate (1675). This research uses historical methods in the form of heuristics, source criticism, interpretation and historiography. The results showed that the Palembang Kingdom was the forerunner to the birth of the Palembang Sultanate. After the collapse of Sriwijaya, Palembang became a royal protection area in Java, namely Majapahit, Demak, Pajang and Mataram. In 1675, Ki Mas Hindi officially adopted the title sultan. This action politically demonstrated that Ki Mas Hindi was equivalent to that of the Mataram ruler and marked the birth of the Palembang Sultanate.Key words: Kingdom, Sultanate, PalembangKesultanan Palembang lahir sebagai akibat dari hubungan yang kurang harmonis antara Palembang dan Mataram. Hal ini menerangkan bahwa dalam perjalanan sejarahnya Palembang memiliki hubungan dengan kerajaan di Jawa. Penelitian ini bertujuan untuk menguraikan hubungan Palembang dengan Jawa sebelum lahirnya Kesultanan Palembang (1675). Penelitian ini menggunakan metode historis berupa heuristik, kritik sumber, interpretasi dan historiografi. Hasil penelitian menunjukkan bahwa Kerajaan Palembang merupakan cikal bakal kelahiran Kesultanan Palembang. Pasca keruntuhan Sriwijaya, Palembang menjadi wilayah protekorat kerajaan di Jawa yaitu Majapahit, Demak, Pajang dan Mataram. Pada tahun 1675, Ki Mas Hindi secara resmi menggunakan gelar sultan. Tindakan ini secara politik menunjukkan bahwa status Ki Mas Hindi setara dengan penguasa Mataram dan menandai kelahiran Kesultanan Palembang. Kata Kunci: Kerajaan, Kesultanan, Palembang